Effect of sodium hypochlorite and calcium hydroxide on fracture resistance of root dentin - Padoin, Karine; Mello, Juliana Heckler; de Carlo Bello, Mariana; Michelon, Carina; Morgental, Renata Dornelles [UNESP]; Bier, Carlos Alexandre Souza (Dental Press International, 2019)
Objective: The aim of this study was to assess the influ-ence of different concentrations of sodium hypochlorite (NaOCl) solution and of calcium hydroxide [Ca(OH)2] paste on the strength of root dentin during endodontic treatment. Methods: Eighty roots of bovine mandibu-lar incisors were randomly assigned to eight groups: C-Control (no intervention); PS-Physiological saline; 1% NaOCl; 5% NaOCl; PS/EDTA; PS/EDTA/Ca(OH)2; 1% NaOCl/EDTA/Ca(OH)2; and 5% NaOCl/EDTA/Ca(OH)2. All groups were prepared with hand K files us-ing the crown-down technique, except for the control group. The irrigating solution in each group was kept in the canal for 2 h, being replaced every 15 min. EDTA was applied for 3 min in the corresponding groups. Ca(OH)2 was kept in the root canals for 30 days. The specimens were subjected to compressive strength testing until fracture in an EMIC universal testing machine. The data were subjected to analysis of variance. The significance level was set as alpha = 0.05. Results: No statistically significant difference was found across the experimental groups (P>0.05). Conclusions: The use of NaOCl for 2h and Ca(OH)2 for 30days did not influence the strength of root dentin.
Keywords: Calcium hydroxide; Endodontics; Root canal irrigants; Sodium hypochlorite